The potential processing of rice husk waste as an alternative media for ornamental plants - Andi Muhamad Iqbal Akbar Asfar; Andi Muhamad Irfan Taufan Asfar; Sharma Thaha; Ady Kurnia; Adji Syaifullah (Riau Journal of Empowerment, 2021)
The problem of rice husk waste as a result of rice processing is a major problem in Sanrego Village, especially in the Pada Elo' Farmer Group. The accumulation of rice husk waste while the land area to accommodate a lot of rice husk waste during the harvest season forced the farmer groups to burn it. However, another problem that arises is the emergence of air pollution and the results of burning rice husk waste are useless because they are not used properly. Therefore, this community service will process the potential of rice husk waste into husk charcoal by providing information, knowledge, and skills on how to process rice husk waste into rice husk charcoal which can be used as an alternative media for ornamental plants which are currently the prima donna. The implementation method consists of three stages, namely Tudang Sipulung, Mario-rio, and Mappesabbi which are taken from the Bugis tradition of having a philosophy of working together, thus directing farmer groups to participate and be fully involved (participatory by doing). The results obtained by the average partner member experienced an 82,5% increase in information and knowledge aspects as well as skills and were able to grow their entrepreneurial spirit, especially processing rice husk waste.